Case Report: A de novo NR2F1 mutation and clinical characteristics of Bosch–Boonstra–Schaaf optic atrophy syndrome in a Chinese patient - Tang, Shuyu; Jiang, Tingshuai; Su, Wenqi; Tang, Binqi; Xiang, Daoman; Zhu, Jie (Frontiers in Medicine, 2025)
PurposeThis study aimed to report the clinical characteristics, genetic findings, and treatment outcomes of a Chinese patient with Bosch–Boonstra–Schaaf optic atrophy syndrome (BBSOAS) caused by a mutation in the NR2F1 gene.MethodA retrospective chart review was conducted, including the patient’s medical history, brain magnetic resonance imaging (MRI), electroencephalogram (EEG), and brainstem auditory evoked potential (BAEP) test results. A detailed ophthalmic examination was recorded, including gaze following, fundus photography, flash-electroretinogram (f-ERG), and flash visual evoked potential (f-VEP). Genetic sequencing results from whole-exome sequencing (WES) were collected.ResultThe patient was an approximately 5-6 years old boy admitted to the hospital due to developmental delay and poor gaze following. Brain MRI revealed a cerebellar cyst, and EEG showed abnormal waveforms. BAEP indicated bilateral auditory conduction pathway impairment. Severe exotropia and optic nerve atrophy were observed in both eyes. f-ERG analysis revealed a moderate-to-severe decrease of dark-adapted (DA) amplitude in the right eye and a mild-to-moderate decrease in the left eye. WES identified a de novo heterozygous missense mutation (NM_005654.6: c.452T>C, p.Met151Thr) in the NR2F1 gene, which was determined to be the cause of the disease. The patient had been receiving neurotrophic treatment since the age of one, but no significant improvement was observed.ConclusionOur report demonstrated the pathogenicity of a variant in the NR2F1 gene, which was previously classified as a variant of uncertain significance or as a likely pathogenic variant, along with a detailed phenotypic characterization. The clinical features and treatment outcomes described here may expand the spectrum of known NR2F1 variants and serve as a reference for understanding this rare disease.